The effect of audit firm tenure in artificial rotation on audit quality - Junaidi Junaidi; Harun Pamungkas Apriyanto; Nurdiono Nurdiono; Eko Suwardi (Universitas Hayam Wuruk Perbanas, 2014)
This study aimed to examine the effect of auditor tenure in artificial rotation on audit quality. Tenure shows the relationship between the audit firms and a client that is measured in years. Artificial rotation of auditor (audit firm) indicates a condition that, conceptually, there has been a change of auditors leading to the auditor relationship with the client to be disconnected, whereas substantive auditor-client relationship is ongoing. Formally, the auditor does not violate the rules and is still able to audit for the same client. Yet, in the long-term, it could affect the audit quality. The longer auditor tenure, the closer auditor-client relationship is. Thus, the auditor accommodates the interests of the client at the client's financial statements, including the practice of discretionary accruals as a proxy for audit quality. The samples were selected by purposive sampling method of the companies listed in Indonesia Stock Exchange from the year 2002-2010, with multiple linear regression approach. It shows that tenure, and total assets do not affect the quality of the audit while the size of the audit firm, and debt statistically have significant effect on audit quality. Future studies may extend the period of observation, and using other audit quality measures, such as fraud, and the propensity of auditor to issue going concern opinion..